A publicidade infantil na mídia televisiva e a violação dos direitos da criança - Anjos, Poliana Cavaglieri Saldanha dos (2017)
This dissertation was developed with the purpose of demonstrating under what circumstances children's advertising inserted by the television media promotes potential violation of the rights of contemporary children. The scope of the theme was an interdisciplinary dialogue in the areas of education, sociology, law, psychology, communication and philosophy, contextualizing the media in the field of cultural studies. Briefly, it presents an analysis of the knowledge of the state of the art, through publications available in the CAPES database, from 2010 to 2015, related to children, consumption, cultural industry, advertising and television media. As the central theme is the insertion of the child into the world of consumption, recognizing its vulnerability, the principles and the action of the competent institutional bodies to act in the control and inspection are debated. It brings together cases of advertising campaigns represented by the self-regulatory advertising council, demonstrating the applicability of the law in the so-called abusive conduct. In an attempt to demonstrate the violation of children's rights, it presents the national standardization, guidelines related to full protection, uses comparative law to verify international regulations, circumscribed in declarations and covenants, as the origin of protection to this subject of law. To substantiate the legal context, it brings jurisprudential decisions of the supreme court on children's advertising in the country, actions and decisions of CONAR, as a self-regulatory, denoting the means to combat violations of children's rights, as well as bills with the initiative to regulate children's advertising.